Vaspin (serpinA12) in obesity, insulin resistance, and inflammation1. (5th March 2014) - Heiker, John T.
<x xml:space="preserve">Abstract</x> While genome‐wide association studies as well as candidate gene studies have revealed a great deal of insight into the contribution of genetics to obesity development and susceptibility, advances in adipose tissue research have substantially changed the understanding of adipose tissue function. Its perception has changed from passive lipid storage tissue to active endocrine organ regulating and modulating whole‐body energy homeostasis and metabolism and inflammatory and immune responses by secreting a multitude of bioactive molecules, termed adipokines. The expression of human vaspin (serpinA12) is positively correlated to body mass index and insulin sensitivity and increases glucose tolerance in vivo, suggesting a compensatory role in response to diminished insulin signaling in obesity. Recently, considerable insight has been gained into vaspin structure, function, and specific target tissue‐dependent effects, and several lines of evidence suggest vaspin as a promising candidate for drug development for the treatment of obesity‐related insulin resistance and inflammation. These will be summarized in this review with a focus on molecular mechanisms and pathways. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.